Perestroik' Art Polylogue : Projet d'art peinture russe contemporain (1985 - 1990). - Janssens, Finita; Grootaers, Jean-Piere; Cultureel Centrum Hasselt (Hasselt : Cultureel Centrum, 1995)
Agroskij, Semion ; Ajzenberg, Valeri ; Babi ; Batisjeva, Natalja ; Batynkov, Konstantine ; Boudaev, Andréi ; Bozjko, Igor ; Daniltsev, Iguenat ; Detkina, Tatiana ; Esoeaoeletov, Askar ; Fonin, Alexandre ; Gor, Evgueni ; Joebin, Joerij ; Karpykov, Igor ; Kaminnik, Igor ; et al.
Cultureel Centrum Hasselt, collectie, 1995.
kunstcatalogus
Keywords: Rusland